Relationship between leukotriene-modifying agent prescriptions dispensed and rate of suicide deaths by county in the US - Schumock GT; Gibbons RD; Lee TA; Joo MJ; Valuck RJ; Stayner LT (Drug, Healthcare and Patient Safety, 2011)
Glen T Schumock1, Robert D Gibbons2, Todd A Lee1,3,4,6, Min J Joo4, Robert J Valuck5, Leslie T Stayner61Center for Pharmacoeconomic Research, and Department of Pharmacy Practice, College of Pharmacy, University of Illinois at Chicago, Chicago, IL, USA; 2Center for Health Statistics, and Departments of Medicine and Health Studies, Pritzker School of Medicine, University of Chicago, Chicago, IL, USA; 3Center for Management of Complex Chronic Care, Hines VA Hospital, Hines, IL, USA; 4Section of Pulmonary, Critical Care, Sleep and Allergy, Department of Medicine, College of Medicine, University of Illinois at Chicago, Chicago, IL, USA; 5Department of Clinical Pharmacy, School of Pharmacy, University of Colorado, Aurora, CO, USA; 6Division of Epidemiology and Biostatistics, School of Public Health, University of Illinois at Chicago, Chicago, IL, USABackground: The US Food and Drug Administration has issued warnings about a potential link between leukotriene receptor-modifying agents (LTMA) and suicide. These warnings are based on case reports and there is controversy about the association. While spontaneous reporting of suicide-related events attributed to LTMA has risen dramatically, these data may be biased by the warnings. The objective of this study was to explore the relationship between LTMA and suicide deaths using event data preceding the Food and Drug Administration warnings.Methods: We conducted a mixed-effects Poisson regression analysis of the association between LTMA prescriptions dispensed and suicide deaths at the county level. Counts of suicide deaths in each US county, stratified by race, age group, gender, and year were obtained from the National Center for Health Statistics for the period January 1, 1999 to December 31, 2006. Counts of LTMA prescriptions dispensed in each US county were obtained from IMS Health Incorporated. The model estimated the overall suicide rate conditional on LTMA use, adjusted for age, gender, race, year, and antidepressant utilization. We also assessed the intracounty and intercounty associations.Results: There were 249,872 suicides in the US between 1999 and 2006, and the annual suicide rate ranged from 11.17 to 11.92 per 100,000 population. There were 118.63, 11.68, and 0.12 million prescriptions dispensed for montelukast, zafirlukast, and zileuton, respectively, between 1999 and 2006. The mean rate of LTMA prescriptions dispensed by county was 42.91 (95% confidence interval [CI] 42.78–43.04), 4.82 (95% CI 4.81–4.84), and 0.05 (95% CI 0.05–0.05) per 1000 for montelukast, zafirlukast, and zileuton, respectively. We found a negative within-county association between the rate of total LTMA prescriptions dispensed and the suicide rate by county (P = 0.0296). This association was primarily driven by montelukast.Conclusion: Our results, while subject to certain limitations, provide preliminary evidence that the association between LTMA and suicide could be different (ie, reduced risk) than that which might be anticipated based on previous warnings. Patient-level research is needed to understand more clearly the association between LTMA and suicide.Keywords: suicide, leukotriene-modifying agents, montelukast, drug safety